Development of Renal Cell Carcinoma in A Young Patient with Ileocecal Crohn’s Disease Under Treatment with Infliximab: Case Report and Review of the Literature - Triantafillidis, John K.; Triantafyllidi, Eleni; Papalois Apostolos Ε. (Archives of Clinical and Medical Case Reports, 2020)
We describe a rare case of a young patient with Crohn’s disease, who accidentally was found to have developed renal cell carcinoma while on treatment with anti-TNF-α biologic agent. The patient was submitted to laparoscopic resection of the tumor. Up to December 2019 he is in perfect condition without receiving any kind of antineoplastic treatment. Clinicians should bear in mind this clinical combination in patients with Crohn’s disease under treatment with biologic anti-TNF-α agents. Because the exact influence of anti-TNF-α biologic agents is largely unclear for now, the continuation of treatment might be a possible option.